2017
DOI: 10.1111/apm.12738
|View full text |Cite
|
Sign up to set email alerts
|

Hypogammaglobulinemia in children: a warning sign to look deeply?

Abstract: This study investigated phenotypic and functional characteristics of lymphocytes in children with common variable immunodeficiency (CVID) and unclassified hypogammaglobulinemia (UH), as well as B-cell subsets in non-consanguineous parents. Blood samples of 30 children, CVID (n = 9), UH (n = 9), healthy donors HD (n = 12), and 19 adults (parents and controls) were labeled by a combination of surface markers to identify CD4, CD8 T-cell and B-cell subpopulations. T-cell cytokine production in children was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…There has been an increasing concern regarding costs of medical assistance for patients with different chronic diseases, including primary immunodeficiencies (PID) (1-7), which are not so rare and often underdiagnosed. In PID, several studies have shown that costs are often associated with delayed diagnosis (8)(9)(10)(11)(12)(13)(14). This generates a series of deleterious events for the patient, their families and the health system, especially regarding hospitalizations due to infection (8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There has been an increasing concern regarding costs of medical assistance for patients with different chronic diseases, including primary immunodeficiencies (PID) (1-7), which are not so rare and often underdiagnosed. In PID, several studies have shown that costs are often associated with delayed diagnosis (8)(9)(10)(11)(12)(13)(14). This generates a series of deleterious events for the patient, their families and the health system, especially regarding hospitalizations due to infection (8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…In PID, several studies have shown that costs are often associated with delayed diagnosis (8)(9)(10)(11)(12)(13)(14). This generates a series of deleterious events for the patient, their families and the health system, especially regarding hospitalizations due to infection (8)(9)(10)(11)(12)(13)(14). The ideal diagnostic approach for PIDs includes extensive immunophenotyping of peripheral lymphocyte subsets, functional and molecular tests, and should be performed as early as possible (15,16).…”
mentioning
confidence: 99%